Cuboid Edema Syndrome Following Fixation of Proximal Fifth Metatarsal Fractures in Professional Athletes. Issue 4 (August 2019) - Roberts, Lauren; Bernasconi, Alessio; Netto, Cesar de Cesar; Elliott, Andrew; Hamilton, William; O'Malley, Martin
Stress fractures of the proximal fifth metatarsal are common injuries in elite athletes. Fixation using an intramedullary screw represents the most popular surgery performed for treating these injuries, with excellent results in most cases. However, multiple reports in the literature highlight the possibility of painful hardware, usually related to the presence of the screw head, following intramedullary fixation In this case report, we outline 4 cases of professional athletes who developed lateral-based foot symptoms following complete healing of their surgically treated proximal fifth metatarsal fractures and were found to have significant cuboid edema on magnetic resonance images. We also outline recommendations regarding specific surgical technique considerations aiming to minimize this possible complication. Level of Evidence: Level V: Case report .